A Multidimensional Model of Sexual Health and Sexual and Prevention Behavior Among Adolescent Women - Hensel, Devon J. (2012)
PURPOSE: Sexual health refers a state of lifespan well-being related to sexuality. Among young people, sexual health has multiple dimensions, including the positive developmental contributions of sexuality, as well as the acquisition of skills pertinent to avoiding adverse sexual outcomes such as unintended pregnancy and sexually transmitted infections (STIs). Existing efforts to understand sexual health, however, have yet to empirically operationalize a multi-dimensional model of sexual health and to evaluate its association to different sexual/prevention behaviors. METHODS: Sexual health dimensions and sexual/prevention behaviors were drawn from a larger longitudinal cohort study of sexual relationships among adolescent women (N =387, 14–17 years). Second order latent variable modeling (AMOS/19.0) evaluated the relationship between sexual health and dimensions and analyzed the effect of sexual health to sexual/prevention outcomes. RESULTS: All first order latent variables were significant indicators of sexual health (β: 0.192 – 0.874, all p < .001). Greater sexual health was significantly associated with sexual abstinence, as well as with more frequent non-coital and vaginal sex, condom use at last sex, a higher proportion of condom-protected events, use of hormonal or other methods of pregnancy control and absence of STI. All models showed good fit. CONCLUSIONS: Sexual health is an empirically coherent structure, in which the totality of its dimensions is significantly linked to a wide range of outcomes, including sexual abstinence, condom use and absence of STI. This means that, regardless of a young person’s experiences, sexual health is an important construct for promoting positive sexual development and for primary prevention.